2022
DOI: 10.1038/s41598-022-19614-6
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor 4-mediated endoplasmic reticulum stress induces intestinal paneth cell damage in mice following CLP-induced sepsis

Abstract: A marked elevation of TLR4 was observed in various organs of septic mice. The mechanism of TLR4 in intestinal epithelial cell damage in sepsis remains unclear. CLP mice models were used to assess the role of TLR4 in intestinal Paneth cell damage by histological, polymerase chain reaction, western-blot analyses. The ileal expression of TLR4 was increased by more than five-fold after CLP. CLP significantly increased 7-day mortality and was associated with a higher murine sepsis score (MSS), closely related with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Delmotte et al found that TNF-α activates the ER stress pathway in human airway smooth muscle cells [38]. Sepsis is an uncontrolled systemic inflammatory response; inflammatory mediators such as TNF-α and IL-6 are elevated in sepsis, and it has been described that ER stress is dramatically induced in sepsis [39][40][41]. Inflammation is considered to be the major predisposing factor for skeletal muscle atrophy, which disturbs the homeostasis of the ER [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Delmotte et al found that TNF-α activates the ER stress pathway in human airway smooth muscle cells [38]. Sepsis is an uncontrolled systemic inflammatory response; inflammatory mediators such as TNF-α and IL-6 are elevated in sepsis, and it has been described that ER stress is dramatically induced in sepsis [39][40][41]. Inflammation is considered to be the major predisposing factor for skeletal muscle atrophy, which disturbs the homeostasis of the ER [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Paneth cells maintain gut mucosal integrity and homeostasis. In an experimental study, septic mice exhibited significantly fewer Paneth cells in the crypt, with disorganized granules or without granules [134]. In murine sepsis, increased ileal expression of TLR4 promoted the depletion of Paneth cells, and reduced lysozyme and defensin alpha 5 (DEF-5) expression exacerbated intestinal damage, and increased mortality rate.…”
Section: Apoptosismentioning
confidence: 99%
“…In murine sepsis, increased ileal expression of TLR4 promoted the depletion of Paneth cells, and reduced lysozyme and defensin alpha 5 (DEF-5) expression exacerbated intestinal damage, and increased mortality rate. It has been suggested that TLR4 mediates the hyperactivation of ER stress, leading to Paneth cell loss and dysfunction during intestinal barrier impairment of sepsis [134].…”
Section: Apoptosismentioning
confidence: 99%
“…Strategies to inhibit the ATF6 signaling pathway may be developed for the treatment of inflammatory bowel diseases ( Stengel et al., 2020 ). The ATF6/CHOP pathway may be associated with intestinal barrier dysfunction during sepsis ( Wang et al., 2022 ). Many studies have shown that inhibition of ATF6 expression can relieve ER stress and exert protective effects on the intestinal barrier function of SeNPs ( Pan et al., 2023 ), chlorogenic acid ( Song et al., 2022a ), and berberine ( Gong et al., 2022 ).…”
Section: Ers Has a Potential Impact On Intestinal Barrier Function Vi...mentioning
confidence: 99%